Carpal Tunnel Syndrome: Diagnostic Usefulness of Ultrasound Measurement of the Median Nerve Area and Quantitative Elastographic Measurement of the Median Nerve Stiffness. (18th August 2019) - Moran, Luz; Royuela, Ana; de Vargas, Alberto Perez; Lopez, Ana; Cepeda, Yamilet; Martinelli, Gianluca
Abstract : Objectives: To correlate the ultrasound (US) measurements of the median nerve cross‐sectional area (CSA) and the measurements of its stiffness by shear wave elastography (SWE) with the severity grade of carpal tunnel syndrome (CTS) using electrodiagnostic testing (EDT) and to determine the cutoff points for CSA and SWE measurements to allow us to discriminate patients with moderate and severe CTS from those with mild or negative EDT findings. Methods: Seventy‐three patients with 105 hands with a clinical suspicion of CTS were studied with US and SWE. We measured the median nerve CSA and elasticity (E) at the tunnel inlet (CSAu and Eu), in the quadratus pronator (CSAo and Eo), and the differences (CSAu – CSAo and Eu – Eo). Results: The nerve area and stiffness increased according to the EDT severity of CTS; the CSA increased proportionally as CTS increased from negative to severe according to EDT, and the stiffness was not different between patients with negative and mild EDT findings but was higher in patients with moderate and severe EDT findings versus negative and mild EDT findings. The cutoff points of a CSAu of 14 mm 2 or greater and an Eu – Eo of 57 kPa or greater together allowed the discrimination of moderate and severe CTS from the rest. Conclusions: The joint use of US and SWE is an alternative to EDT in the clinical management and treatment of patients with a clinical suspicion of CTS.